Physical functioning of below knee amputees in Sri Lanka: A preliminary study - Kisokanth, G.; Nadeeshani, K. M. D.; Prathapan, S. (My University, 2020)
Limb amputations are lifesaving yet devastating for the amputees when adapting physically to changes after an amputation. Few studies in this area have been conducted in the Sri Lankan context despite its importance. The aim of the study was to assess the physical functioning of the unilateral lower limb amputees in Sri Lanka. A cross-sectional descriptive study was conducted and 100 male and female amputees, aged 20-80 years with a unilateral lower limb amputation representing all rehabilitation settings in Sri Lanka were included using simple random sampling. Assessment was carried out using the physical functioning subscale of the short form health survey (SF-36) after pretesting. Lower scores indicated lower physical functioning. Descriptive and inferential statistics were used to analyze data using SPSS 21. Most of the participants (70%) were males and 41% of them were aged 41-60 years. Nearly 54% of them had transtibial amputations. The mean score for the physical functioning was 61.3 (±25.5). Activity limitations were categorized as; limited a lot, limited a little or not limited at all. The percentages of participant responses according to the above categorization was consecutively 35%; 36%; 29% for vigorous activities, 13%; 42%; 45% for moderate activities, 11%; 32%; 57% for lifting or carrying groceries, 18%; 47%; 35% for climbing of stairs, 9%; 29%; 62% for bending/kneeling, 25%; 42%; 33% for walking several miles, 8%; 29%; 63% for walking one block and 17%; 43%; 40% for self-care activities. Physical functioning was significantly associated with education level (p=0.01), level of amputation (p=0.04) and marital status (p=0.00) and was not associated with age (p=0.14), income (p=0.21), job (p=0.05) and financial help (p=0.27). The physical functioning among the unilateral lower limb amputees were higher than the average (50%). In order to improve physical activity further among below knee amputees, home based physical exercise programmes can be introduced.

Limb amputations are lifesaving yet devastating for the amputees when adapting physically to changes after an amputation. Few studies in this area have been conducted in the Sri Lankan context despite its importance. The aim of the study was to assess the physical functioning of the unilateral lower limb amputees in Sri Lanka. A cross-sectional descriptive study was conducted and 100 male and female amputees, aged 20-80 years with a unilateral lower limb amputation representing all rehabilitation settings in Sri Lanka were included using simple random sampling. Assessment was carried out using the physical functioning subscale of the short form health survey (SF-36) after pretesting. Lower scores indicated lower physical functioning. Descriptive and inferential statistics were used to analyze data using SPSS 21. Most of the participants (70%) were males and 41% of them were aged 41-60 years. Nearly 54% of them had transtibial amputations. The mean score for the physical functioning was 61.3 (±25.5). Activity limitations were categorized as; limited a lot, limited a little or not limited at all. The percentages of participant responses according to the above categorization was consecutively 35%; 36%; 29% for vigorous activities, 13%; 42%; 45% for moderate activities, 11%; 32%; 57% for lifting or carrying groceries, 18%; 47%; 35% for climbing of stairs, 9%; 29%; 62% for bending/kneeling, 25%; 42%; 33% for walking several miles, 8%; 29%; 63% for walking one block and 17%; 43%; 40% for self-care activities. Physical functioning was significantly associated with education level (p=0.01), level of amputation (p=0.04) and marital status (p=0.00) and was not associated with age (p=0.14), income (p=0.21), job (p=0.05) and financial help (p=0.27). The physical functioning among the unilateral lower limb amputees were higher than the average (50%). In order to improve physical activity further among below knee amputees, home based physical exercise programmes can be introduced. Keywords: Amputation, lower limb amputees, physical functioning, Sri Lanka
Keywords: Amputation; lower limb amputees; physical functioning; Sri Lanka